Control Of Anticoagulation Therapy in Atrial Fibrillation (COAT-AF Study) in Real Clinical Practice - A. A. Zarudsky; A. A. Gavrilova; Т. S. Filinichenko (Рациональная фармакотерапия в кардиологии)
Aim. To study the frequency of prescribing anticoagulant therapy in outpatients with AF in accordance with clinical guidelines.Material and methods. Control Of Anticoagulation Therapy in Atrial Fibrillation (COAT-AF) observational study was conducted at the Saint Joasaph Belgorod Regional Clinical Hospital from January 1, 2016 to December 31, 2017. Patients with AF represented 15.5% of all patients admitted to cardiology department N1. 429 patients were included into the study: 203 women, 226 men; aged of 62.55±11.12 years. Exclusion criteria were mitral stenosis, mechanic prosthetic valve, first episode of AF. CHA2DS2-VASc score was used in all patients for calculation the risk of ischemic stroke and systemic thromboembolism. For patients that were treated by warfarin international normalization ratio (INR) was assessed at admission and discharge from the hospital.Results. From 429 patients 35 had 1 point according to the CHA2DS2-VASc scale, 393 (91.6%) patients had ≥2 points. Only 1 patient had 0 point. Therefore, most patients had absolute indications to anticoagulant therapy. At admission 60 (14%) patients received new oral anticoagulants (NOACs), 213 (49.6%) – warfarin, 156 (36.4%) – did not take any oral anticoagulant. Among patients receiving warfarin only 36 (8.4%) had target INR at admission. Therefore, effective anticoagulant therapy was observed only in 22.4% of patients in real clinical practice. Analyzing anticoagulant therapy in 2016 and 2017 we found a significant increase in NOAC prescription from 10.4% in 2016 to 18.9% in 2017 (p=0.0193).Conclusion. Our data reflects important gaps of anticoagulant therapy in real clinical practice. We compare our results with other Russian registries that included AF-patients. Data at admission and discharge suggests that there are great possibilities for optimization of anticoagulant therapy mainly with NOACs.